Hospice Interdisciplinary Team Processes and Effectiveness - Hale, Beth Ann (The University of Arizona., 2007)
The purpose of this research was to test a causal model of interdisciplinary hospice processes and effectiveness. This research examined the impact of organization and team level structure constructs (organizational culture, team complexity, and team leadership) on hospice interdisciplinary team processes and subsequent influence on perceived team effectiveness. The relationships among perceived team effectiveness, team task satisfaction, and family satisfaction with hospice care were also examined.The sample consisted of 41 hospice interdisciplinary teams drawn from two hospice organizations in a southwestern city of the United States. Participants included 410 interdisciplinary team members and 32 hospice team leaders. Measures used in this research were adapted from instruments previously used in non-hospice settings. Data were collected through self-report surveys. Psychometric properties of all instruments were performed at the individual and group level. Psychometric properties of all but three scales (Hospice Organizational Culture: Group Culture, Hierarchical Culture, and Developmental Culture) exhibited reliability and evidence of validity as group measures.Four hypothesized relationships were supported, and six nonhypothesized relationships were significant in the model. All team processes except conflict management had positive direct effects on perceived team effectiveness. Perceived team effectiveness had a positive direct effect on team task satisfaction, and team task satisfaction was positively correlated with family satisfaction with hospice care in a limited sample. The proposed structural factors (hospice organizational culture, team complexity, and team leadership) did not impact hospice interdisciplinary team processes or team effectiveness. Approximately sixty-five percent of the variance in team effectiveness was explained by team hospice experience and team processes (leadership, communication, and coordination). Nearly fifty percent of variance in team task satisfaction was explained by the processes used for conflict management and perceived team effectiveness.Relationships identified in this research are viewed as preliminary. Future research should modify and re-examine model relationships with a larger sample drawn from diverse hospice organizations. In addition, structural variables influencing the hospice interdisciplinary team need to be re-examined for appropriateness and conceptual relevance. However, this study provided a foundation for understanding hospice interdisciplinary team processes and the influence of these processes on team and family satisfaction.